Is home‐based pelvic floor muscle training effective in treatment of urinary incontinence after birth in primiparous women? A randomized controlled trial. (10th June 2013) - Åhlund, Susanne; Nordgren, Birgitta; Wilander, Eva‐Lotta; Wiklund, Ingela; Fridén, Cecilia
Abstract Objective To assess the effect of pelvic floor muscle training (PFMT) on pelvic floor muscle strength and urinary incontinence (UI) in primiparous women who underwent a home training program between three and 9 months after delivery. Design Randomized controlled trial. Population One hundred primiparous women were consecutively recruited from four different antenatal clinics in the urban area of Stockholm, Sweden. Women with UI who had undergone normal term singleton vaginal delivery, 10–16 weeks postpartum were randomly allocated to either intervention or control group. Methods Maximally voluntary contraction (MVC) and endurance were measured with a perionometer. The Oxford grading scale was used to manually estimate the strength of the pelvic floor muscle and self‐reported symptoms of UI was registered through the Bristol Female Lower Urinary Tract Symptoms Module (ICIQ FLUTS) questionnaire. Main outcome measures Maximally voluntary contraction of the pelvic floor muscle measured with a perionometer. Results Maximally voluntary contraction increased significantly in both groups between baseline and follow up (p < 0.05). The median MVC in cmHg for the intervention and control group was 16.2 and 12.1 at baseline and 26.0 and 18.2 at follow up, respectively. The median endurance, in seconds, for the intervention and control group was 9.6 and 12.0 at baseline and 26.7 and 23.4 at follow up, respectively. Pelvic floor muscle strength measured with the Oxford Scale increased significantly in both groups between baseline and follow up (p < 0.05). Conclusion The results indicate that home‐based PFMT is effective. However, written training instructions were as efficient as home‐based training with follow up visits every sixth week.